Some medical and other risk factors for current cesarean section in a Jakarta hospital (Medical Journal of Indonesia, 2001)
For the last year the prevalence of cesarean section (CS) increased in several countries as well as in Indonesia. In Indonesia there was no comprehensive study on risk factors related to CS. This case-control study was conducted at Fatmawati Hospital in Jakarta from 1 July 200 until 31 January 2001. Data was extracted from available medical records. Ceserean section was defined as a delivery through laparotomy. The control group consisted of subjects having vaginal deliveries. For each cases were selected randomly a control based on the date before or after 18 October 2000. Subject who had fetal distress had 544-folds increased risk to be CS relative to those who did not have fetal distress [adjusted odds ratio (OR) = 544.86; 95% confidence intervals (CI) = 71.85- 4131.78]. Furthermore, relative those who did not have dystocia, those who had dystocia had 143 times increased risk to be CS (adjusted OR = 52.86; 95% CI = 52.86 - 391.17). In term of previous CS, subjects who ever had previous CS had 30 times increased risk to be CS compared with the subjects who never had CS (adjusted OR = 30.23; 95% CI = 12.06 - 75.57). In contrast, compared with those who non cash payment, those who paid in cash had a lowered risk of 80% (adjusted OR = 0.20; 95% CI = 0.11-0.34). In conclusion, previous CS, dystocia, pre eclampsia, other medical indications, fetal distress, and non cash hospitalization expences increased risk of CS. (Med J Indones 2001; 10: 230-4)